2021
DOI: 10.1093/nar/gkab785
|View full text |Cite
|
Sign up to set email alerts
|

XAB2 promotes Ku eviction from single-ended DNA double-strand breaks independently of the ATM kinase

Abstract: Replication-associated single-ended DNA double-strand breaks (seDSBs) are repaired predominantly through RAD51-mediated homologous recombination (HR). Removal of the non-homologous end-joining (NHEJ) factor Ku from resected seDSB ends is crucial for HR. The coordinated actions of MRE11-CtIP nuclease activities orchestrated by ATM define one pathway for Ku eviction. Here, we identify the pre-mRNA splicing protein XAB2 as a factor required for resistance to seDSBs induced by the chemotherapeutic alkylator temozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Not surprisingly, the pro-oncogenic role of RAD52 is especially pronounced in cancer cells that are deficient in DDR pathways, like ATM-deficient cancers ( Treuner et al, 2004 ). But the most remarkable pro-cancer RAD52 phenotype is seen in cancer cells deficient in any of the following DNA repair proteins: BRCA1, BRCA2, PALB2, XAB2 or RAD51 paralogs: RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3 ( Feng et al, 2011 ; Chun et al, 2013 ; Lok et al, 2013 ; Sharma et al, 2021 ). Powell’s group showed that cells in which one of these proteins were mutated or depleted became dependent on RAD52 for viability; thus, mutations in RAD52 are synthetically lethal with mutations/depletion in these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the pro-oncogenic role of RAD52 is especially pronounced in cancer cells that are deficient in DDR pathways, like ATM-deficient cancers ( Treuner et al, 2004 ). But the most remarkable pro-cancer RAD52 phenotype is seen in cancer cells deficient in any of the following DNA repair proteins: BRCA1, BRCA2, PALB2, XAB2 or RAD51 paralogs: RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3 ( Feng et al, 2011 ; Chun et al, 2013 ; Lok et al, 2013 ; Sharma et al, 2021 ). Powell’s group showed that cells in which one of these proteins were mutated or depleted became dependent on RAD52 for viability; thus, mutations in RAD52 are synthetically lethal with mutations/depletion in these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Combined depletion experiments did not lead to enhanced defects in HR or SSA suggesting that XAB2, ISY1 and PRP19 could function together to promote DSB repair. More recently, XAB2 was also identified in an shRNA-targeted screen for genes involved in temozolomide (TMZ) resistance [ 122 ]. XAB2 depletion impaired DSB repair and fork progression in the presence of CPT suggesting a role in single-ended DSB repair.…”
Section: Regulation Of Dsb Resection By Ntc Complex Membersmentioning
confidence: 99%
“…However, fully active HR outcompetes NHEJ for the repair of seDSBs in S/G2 [ 61 ]. Several studies have underlined the involvement of HR in the repair of lesions resulting from O 6 -meG adducts [ 62 , 63 , 64 ].…”
Section: Dna Repair Mechanisms Promoting Resistance To Ir and Alkylating Agent Therapymentioning
confidence: 99%
“…At the same time, our catalogue of small molecule inhibitors targeting DNA repair is expanding rapidly [ 225 , 226 , 227 , 228 ] while novel targets are being discovered for the sensitization of glioma cells to radio- and chemotherapy [ 21 , 22 ]. These include RAD52 whose depletion led to TMZ hypersensitivity in GBM cells [ 64 ]. Carruthers et al found that adult GBM stem-like cells display high levels of DNA replication stress driving constitutive DDR activation and radiation resistance [ 229 ].…”
Section: Strategies Targeting Chromatin Dynamics and Dna Repair In Phggsmentioning
confidence: 99%